Optimizing The Integrity of The Golfpress in Providing Services at Sentul Highland Golf Club - Heru Suheryadi; Imas Masriah; Anisa Pangestika; Asmawih; Nuryadina August Rini (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study explores the essential role of caddy integrity in optimizing customer service at Sentul Highlands Golf Club. The research focuses on the competencies, attitudes, and responsibilities required to deliver excellent service and enhance customer loyalty. Research methods: This study employs a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The primary informant is the golf course operations supervisor. The data were analyzed through data reduction, presentation, and conclusion drawing. Result and discussion: The findings indicate that caddy integrity comprises three leading indicators: honesty, trustworthiness, and responsibility. High levels of integrity significantly impact service quality, ensuring a comfortable playing experience for customers and maintaining the company's professional image. Optimization efforts include regular briefings, performance evaluation forms, periodic integrity training, and monthly assessments. Implication: These findings highlight the importance of field management in strengthening a culture of integrity among caddies through continuous training, evaluation, and coaching. Such efforts are a strategic approach to maintaining service quality in the competitive golf industry.